2023
DOI: 10.1002/aoc.7087
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐proliferative potential of copper(I) acylthiourea complexes with triphenylphosphine against breast cancer cells

Abstract: We report the synthesis of five new Cu(I) acylthiourea complexes (C1–C5) bearing the general formula [Cu(L‐R)Cl (PPh3)2] [L = monodentate acylthiourea ligand, R = C6H5 (L1), C6H4CH3(o) (L2), C6H4OCH2CH3(p) (L3), C10H7 (L4) or C6H4Cl(p) (L5)]. All the complexes were characterized by analytical and spectroscopic tools. The complexes (C1–C5) exhibited a distorted tetrahedral geometry as inferred from the single crystal X‐ray diffraction study. The complexes were subjected to interact with the biomolecules (calf t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…So far, many studies have been reported on the anti‐tumor activity of organometallic compounds such as platinum, rhodium, gold, iridium, ruthenium, palladium, copper, etc [38–42] . Mainly in these studies, the emphasis is on introducing derivatives that are more effective compared to cisplatin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, many studies have been reported on the anti‐tumor activity of organometallic compounds such as platinum, rhodium, gold, iridium, ruthenium, palladium, copper, etc [38–42] . Mainly in these studies, the emphasis is on introducing derivatives that are more effective compared to cisplatin.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, some novel palladium(II) complexes were synthesized by Haribabu et al., [42] which they exerts their mechanism of action through induction of apoptosis via ROS‐mediated mitochondrial signaling pathway. The mechanism of action of 1 a – 1 c complexes, has a lot in common with this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure for synthesizing indole‐based TSCs (L1–L4) is available in the literature [57] . The copper(I) precursor was synthesized using a method reported in the literature [73] . UV‐Vis spectra of the complexes ( 1 – 4 ) in water (with 1 % DMSO) were recorded over 24 h to assess their stability.…”
Section: Methodsmentioning
confidence: 99%
“…An enhancement in absorbance was seen upon the addition of the complexes at 280 nm, which indicated the static nature of binding between BSA and complexes (Figure S65). 42 Further, the interaction between the complexes and BSA was studied through fluorescence spectroscopy. The fluorescence spectra were recorded in the range of 290−500 nm upon excitation at 280 nm.…”
Section: Importantly Trans-[imi-h]-[rucl 4 (Imi) 2 ] and Trans-[ind-h...mentioning
confidence: 99%